Correlation of Myopia with Physical Exercise and Sleep Habits among Suburban Adolescents - Yuan Qu; Jianfeng Yu; Wei Xia; Huijuan Cai (Journal of Ophthalmology)
Purpose. To analyse the correlation of myopia with physical exercise and sleep habits to explore the possible risk or protective factors of juvenile myopia. Methods. This study was a retrospective cross-sectional study. A total of 1831 students aged 11–18 years from five schools in Qingpu completed questionnaires from 2018 to 2019; the students were divided into the nonmyopia group and the myopia group, with students in the myopia group having myopia in at least one eye. Based on the chi-square test, the variables with statistical significance were selected for the logistic regression analysis. Adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were determined. Results. Myopia was positively associated with older age (OR = 2.216, 95% CI: 1.720–2.855), having a parent with myopia (father: OR = 2.463, 95% CI: 1.900–3.193; mother: OR = 2.853, 95% CI: 2.232–3.646), and a late bedtime during holidays (before 10 pm: p = 0.002; 10 pm-11 pm: OR = 1.516, 95% CI: 1.095–2.100; 11 pm-12 am: OR = 1.966, 95% CI: 1.383–2.795), but negatively correlated with male gender (OR = 0.693, 95% CI: 0.549–0.876), a late daily wake time (OR = 0.782, 95% CI: 0.621–0.985), and having more days per week of outdoor activities during the semester (OR = 0.764, 95% CI: 0.597–0.978). After adjustment for demographic characteristics, myopia was positively associated with a late bedtime during holidays (before 10 pm: p = 0.003; 10 pm-11 pm: OR = 1.570, 95% CI: 1.076–2.289; 11 pm-12 am: OR = 2.173, 95% CI: 1.451–3.253; after 12 am: OR = 1.786, 95% CI: 1.093–2.919), but negatively correlated with a late daily wake time during the semester (OR = 0.761, 95% CI: 0.581–0.997). Conclusion. The association of outdoor exercise with myopia among Chinese suburban adolescents does not seem to be as strong as that of sleep habits. Future research could seek to provide consistent evidence for a potential association between myopia and sleep habits.